The Challenge of Financing Health Care in the Current Crisis An Analysis Based on the OECD Data - Scherer, Peter (OECD Health Working Papers, 2010)
The ratio of health expenditure to GDP, which in macroeconomic terms is an indicator which summarises the financing needs of a national health system, is likely to rise in countries for which the GDP falls. Over the past four decades, health expenditure has risen in most countries at a faster rate than GDP, leading to a rise in the expenditure ratio. Fluctuations in this ratio can come about through fluctuations in either of its components. In some cases, notably the USA, GDP variation is the main origin of changes in the ratio, but in the majority of countries health expenditure variation is more important. The experience of countries which did reduce health expenditure after previous recessions suggests that such reductions are short-lived, and demand for health services results over time in a revival of health expenditure growth